Sensitivity and specificity of waist to height ratio in obesity - Tysa Runingsari (ARGIPA (Arsip Gizi dan Pangan), 2018)
The most recommended obesity measurement is using the Body Mass Index (BMI) method as a gold standard in predicting obesity and the risk of illness. Another alternative method which can also be used is Waist-to-Height Ratio (WHtR). Somehow, lack of sensitivity and specificity data comparison between WHtR and BMI is still remaining unknown. Therefore, the purpose of this study was to determine the sensitivity (Se) and specificity (SP) WHtR and BMI against the risk of obesity in adults. The design of this study was cross sectional. The subjects of the study were Nutrition Sciences students of Diponegoro University which amounted to 50 people with age range 19-39 years. The sampling technique used was purposive sampling. The data obtained then tested normality with Kolmogorov-Smirnov test which then continued with sensitivity test and specificity by using Receiver Operator Characteristic Curve (ROC). The results of this study showed a sensitivity value of 100% and a specificity of 59,52% for the measurement of the Waist-to-Height Ratio (WHtR). The AUC value of this WHtR indicated that the WHtR measure was very good (0,960) to detect the risk of obesity. WHtR has excellent ability and is as good as BMI in detecting obesity. The WHtR method can be used as an alternative method used in classifying obesity, especially central obesity. Keywords: BMI, Sensitivity and Specificity, WHtR